2020
DOI: 10.3102/0034654319899707
|View full text |Cite
|
Sign up to set email alerts
|

First-Generation College Students as Academic Learners: A Systematic Review

Abstract: The literature on first-generation college students largely focuses on the challenges and barriers they may experience in college. Yet, we do not have a clear understanding of who these students are as learners. To address this gap, this systematic review examines how scholars study and conceptualize first-generation college students as learners. We found the majority of the literature we reviewed conceptualized them as learners based on their academic performance and the influence of cultures on their learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
123
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 95 publications
(152 reference statements)
3
123
0
7
Order By: Relevance
“…Systematic reviews are commonly described as clear, unambiguous, and precise ways to review literature and enable replication of the search process (Moher et al, 2015) and can be beneficial for identifying gaps and pointing to future research directions (Ives & Castillo-Montoya, 2020; Petticrew & Roberts, 2008). By using a predefined methodological approach and applying explicit inclusion and exclusion criteria, they offer a comprehensive identification, classification, and synthesis of the core area of research under investigation (Hofmann et al, 2011).…”
Section: An Overview Of Previous Systematic Reviews On Diversity and mentioning
confidence: 99%
“…Systematic reviews are commonly described as clear, unambiguous, and precise ways to review literature and enable replication of the search process (Moher et al, 2015) and can be beneficial for identifying gaps and pointing to future research directions (Ives & Castillo-Montoya, 2020; Petticrew & Roberts, 2008). By using a predefined methodological approach and applying explicit inclusion and exclusion criteria, they offer a comprehensive identification, classification, and synthesis of the core area of research under investigation (Hofmann et al, 2011).…”
Section: An Overview Of Previous Systematic Reviews On Diversity and mentioning
confidence: 99%
“…Finally, a prospective first-generation college student group intervention, while promising in its potential for positive impacts, is in no way an adequate replacement for the important work necessary for all educators, school counselors included, in redressing the racial inequities embedded across America’s educational systems (Cook et al, 2018). We also recognize that the bulk of the literature on first-generation college students has assumed a deficit or assimilationist perspective of these youth, rather than recognizing that the unique traits and experiences of first-generation students could serve to reshape more inclusive higher education policies and practices for all (Ives & Castillo-Montoya, 2020). Nonetheless, brief, tailored interventions such as the group described in this study may offer an additional and meaningful college preparatory resource to aid youth of color in overcoming barriers in accessing and achieving an advanced degree.…”
Section: Discussionmentioning
confidence: 99%
“…More recent scholarship has sought to counterbalance these troubling realities by identifying the many strengths and resources that first-generation college students of color draw upon to thrive in school. Examples include students' pride in personal identities such as one's faith, race, first-generation status, or immigration histories and cultures (Havlik et al, 2017;Ives & Castillo-Montoya, 2020;Wilkins, 2014), and the ability to form and draw upon support networks including teachers, family, community, extracurricular groups, and campus-situated mentors and peers (Demetriou et al, 2017;Havlik et al, 2017). Studies also have shown that the idea of being the first in one's family to achieve a college education can be inspiring and act as a motivator for first-generation students, resulting in a sense of pride and, ultimately, success (Burger & Naude, 2019;Havlik et al, 2017).…”
mentioning
confidence: 99%
“…However, knowledge specifically on the experiences and perceptions of FGMFSs as learners in higher education is lacking (Ives & Castillo-Montoya, 2020); the literature mainly focuses on the struggles and adverse outcomes of FGCSs, while few studies have focused on the experiences of successful students in this population (Demetriou et al, 2017) or examined the factors that promote their academic success in Finland. Makrooni (2019) described the perceptions and experiences of FGMFSs as they travel the educational path to higher education in Finland, using three main categories: family values, institutional values, and friendship.…”
Section: First-generation Students In Higher Educationmentioning
confidence: 99%
“…However, a segment of this population that has not received much attention is firstgeneration migrant family students (FGMFSs), higher education students who belong to migrant families, and whose parents do not have a university degree. In the context of higher education in Finland, few studies have focused on the experiences and perceptions of successful FGMFSs (Makrooni, 2019(Makrooni, , 2020 compared to the US, where several studies have focused on the first-generation college students (Ives & Castillo-Montoya, 2020;Quinn et al, 2019). The topics have dealt with, for example, their persistence and completion of college studies (Holt & Winter, 2018), and impact factors increasing the retention (Pellew, 2016).…”
mentioning
confidence: 99%